UPAYA MENINGKATKAN LITERASI SISWA MENGGUNAKAN MEDIA LAGU PADA MATA PELAJARAN BAHASA INDONESIA MATERI TANDA BACA KELAS IV UPT SDN 060909 MEDAN - Kasuma Harahap; Mutia Febriyan; Farida Yusni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to find out the picture of increasing students literacy in punctuation material using song media in class IV of UPT SDN 060909 Medan for the 2024-2025 academic year. The research method is Classroom Action Research (PTK), the object of this research is all clas IV students OF UPT SDN 060909 Medan. Next the subjects were determined to be 30 people. The instruments used as data collection tools were tests, observation, and documentation. Then the research data was processed using data analysis techniques, namely the use of the maten song media. Punctuation in class IV of UPT SDN 060909 Medan increased, marked by increased student literacy through the use of media. Song, which can be proven in cycle I obtained a percentage of 46,6 % , in cycle II the percentage was 80 %, from cycle I to cycle II there was increase of 33,4 %, teacher observation through the use of song media in the class IV at UPT SDN 060909 Medan, which can be seen from the percentage of observation of teacher respondets in cycle I of 75 % with the “enoungh” category and cycle II 83,3 % with the “good” category, and cycle I to cycle II experienced an increase of 8,3 % and student learning activities through the ude of song media in cycle I 72,2 % with the “enough” category to cycle II 80,5 % with “good” category, experienced an increase of 8,3 %.